MOVING CLASS AS CLASSROOM MANAGEMENT FOR EFL LEARNERS - M Fatkhu Arifin; Lilia Indriani (Indonesian EFL Journal, 2022)
This study was addressed to answer the following questions; 1) what is the role of moving class in English Language Teaching? and 2) what are the advantages and disadvantages of the moving class system? The research method used in this study was descriptive qualitative with observation as the data collection technique. Beside observation, Focus Group Discussion and interview were also taken to strengthen the data. The data were analysed, interpreted and were used in the presentation and discussion of the findings. From the result, it can be concluded that Moving Class system has a significant role in English Language Teaching. It gives the ELT teachers more space to control their classroom to be in accordance to the subject they taught. A fully-controlled classroom will provides an effective and efficient learning process. Implementing Moving Class system can be beneficial for the implementer especially in Boarding School. It can reduce the possibility of sleeping students during the class. Besides that, Moving Class system can be as an orientation to the college system.Keywords: moving class; classroom management; EFL.